Epidermal Growth Factor-Dependent Phosphorylation and Ubiquitinylation of MAGE-11 Regulates Its Interaction with the Androgen Receptor - Bai, Suxia (American Society for Microbiology (ASM), 2008)
The androgen receptor (AR) is a ligand-activated transcription factor that interacts with coregulatory proteins during androgen-dependent gene regulation. Melanoma antigen gene protein 11 (MAGE-11) is an AR coregulator that specifically binds the AR NH(2)-terminal FXXLF motif and modulates the AR NH(2)- and carboxyl-terminal N/C interaction to increase AR transcriptional activity. Here we demonstrate that epidermal growth factor (EGF) signaling increases androgen-dependent AR transcriptional activity through the posttranslational modification of MAGE-11. EGF in the presence of dihydrotestosterone stabilizes the AR-MAGE complex through the site-specific phosphorylation of MAGE-11 at Thr-360 and ubiquitinylation at Lys-240 and Lys-245. The time-dependent EGF-induced increase in AR transcriptional activity by MAGE-11 is mediated through AR activation functions 1 and 2 in association with the increased turnover of AR and MAGE-11. The results reveal a dynamic mechanism whereby growth factor signaling increases AR transcriptional activity through the covalent modification of an AR-specific coregulatory protein. Sequence conservation of the MAGE-11 phosphorylation and ubiquitinylation sites throughout the MAGE gene family suggests common regulatory mechanisms for this group of cancer-testis antigens.